Serological Diagnosis of Ovine Enzootic Abortion by Enzyme-Linked Immunosorbent Assay with a Recombinant Protein Fragment of the Polymorphic Outer Membrane Protein POMP90 of Chlamydophila abortus - Longbottom, David (American Society for Microbiology, 2002)
Ovine enzootic abortion (OEA) resulting from infection of sheep and goats with Chlamydophila abortus is of major economic importance worldwide. Over the last 50 years the serological diagnosis of infection has been based mainly on the complement fixation test (CFT), which lacks both sensitivity and specificity because of cross-reactive antibodies to other gram-negative bacteria, including another common chlamydial pathogen of sheep, Chlamydophila pecorum. In the present study, a series of overlapping recombinant antigens representing the polymorphic outer membrane protein POMP90 of C. abortus was assessed by enzyme-linked immunosorbent assay (ELISA) with a panel of 143 serum samples from sheep experimentally infected with C. abortus, from sheep clinically free of OEA, and from specific-pathogen-free lambs experimentally infected with different subtypes of C. pecorum. The results were compared to those obtained by CFT and another recently described test, an indirect ELISA (iELISA) with the recombinant OMP91B (rOMP91B) fragment (rOMP91B iELISA) (D. Longbottom, E. Psarrou, M. Livingstone, and E. Vretou, FEMS Microbiol. Lett. 195:157-161, 2001). The rOMP90-3 and rOMP90-4 ELISAs were identified as being more sensitive and specific than CFT. Assays with both fragments were evaluated further with a panel of 294 field serum samples from flocks with documented histories of abortion, from flocks with no clinical histories of abortion but which had a high proportion of samples seropositive by CFT, and from animals with no histories of abortion but from which various C. pecorum subtypes had been isolated. ELISAs with both POMP90 fragments outperformed CFT with serum samples from C. pecorum-infected animals, producing no false-positive results. However, the ELISA with the rOMP90-4 fragment appeared to be more sensitive than the one with rOMP90-3, as it identified more of the OEA-positive samples. The ELISA with the rOMP90-4 fragment was also able to identify apparently healthy animals that were infected with an enteric strain of C. abortus in flocks that were probably infected with both enteric C. abortus and C. pecorum strains. The identification of animals infected with enteric C. abortus is extremely important in controlling the spread of OEA. Overall, the new rOMP90-4 ELISA was found to be a more sensitive and specific test than CFT for differentiating animals infected with C. abortus from those infected with C. pecorum.